HUBUNGAN GAYA KEPEMIMPINAN DENGAN KINERJA KARYAWAN (STUDI PADA PT. BANK BNI SYARIAH CABANG PEKANBARU) - Afrida "; Meyzi Herianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This research is motivated because of the work of employees who almost daily are not always completed on time , sometimes there is still a job of another employee who cause problems and absenteeism levels are still high . Thus the role of leadership is needed in improving their performance . The purpose of this study was to determine the style of leadership and the performance of employees of PT . Bank BNI Syariah Branch Pekanbaru and to determine the relationship of leadership style with the performance of the employees of PT . Bank BNI Syariah Branch Pekanbaru . The results showed that the leadership styles used by leaders of PT . Bank BNI Syariah Branch Pekanbaru tend to use a leadership style where the leader of the delegation of the work delegated authority to hand over full responsibility for the execution of the work to subordinates , but in practice the leadership also use autocratic and participative leadership style . Moreover the performance of the employees still have shortcomings in terms of work , work discipline , the possession of work and cooperation . From the statistical analysis it is known that the style of leadership has a strong connection with the performance of the employees of PT . Bank BNI Syariah Branch Pekanbaru.Keywords : leadership style, employee performance, PT. Bank BNI Syariah Branch Pekanbaru